1994
DOI: 10.1002/ijc.2910560419
|View full text |Cite
|
Sign up to set email alerts
|

Mimicry of a carcinoembryonic antigen epitope by a rat monoclonal anti‐idiotype antibody

Abstract: Anti-idiotype antibodies (Ab2) that immunologically mimic tumor antigens are auspicious agents for the active immunization of cancer patients. We have developed W12, a rat monoclonal IgG1 Ab2 to MN-14, a murine anti-carcinoembryonic antigen (CEA) monoclonal antibody. W12 is specific for MN-14 and does not react with other isotype-matched anti-CEA monoclonal antibodies. Moreover, W12 inhibits the binding between MN-14 and CEA. Anti-CEA antibodies can be induced by immunization with W12 (but not with control rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Because the noncovalent complex is injected at a concentration below the K d determined for the a 2 b association by equilibrium gel filtration, the DDD1͞AD1 complex falls apart during and immediately after injection, resulting in Ϸ50% decrease in the response units (RU) obtained from binding to the immobilized HSG when compared with that of TF2. Subsequent injections of WI2 IgG, a rat antiidiotype to hMN-14 (21), demonstrated that only TF2 contained the hMN-14 component that was tightly associated with the h679 component, as indicated by an additional increase in RU. If the WI2 binding is allowed to approach saturation, the stoichiometry of the binding between TF2 and WI2 can be determined by using the formula (RU WI2 ͞ RU TF2 ) ϫ (MW TF2 ͞MW WI2 ) .…”
Section: Bispecific Trivalent Structures Composed Of Three Stably Linmentioning
confidence: 99%
“…Because the noncovalent complex is injected at a concentration below the K d determined for the a 2 b association by equilibrium gel filtration, the DDD1͞AD1 complex falls apart during and immediately after injection, resulting in Ϸ50% decrease in the response units (RU) obtained from binding to the immobilized HSG when compared with that of TF2. Subsequent injections of WI2 IgG, a rat antiidiotype to hMN-14 (21), demonstrated that only TF2 contained the hMN-14 component that was tightly associated with the h679 component, as indicated by an additional increase in RU. If the WI2 binding is allowed to approach saturation, the stoichiometry of the binding between TF2 and WI2 can be determined by using the formula (RU WI2 ͞ RU TF2 ) ϫ (MW TF2 ͞MW WI2 ) .…”
Section: Bispecific Trivalent Structures Composed Of Three Stably Linmentioning
confidence: 99%
“…22) The traditional criteria for the determination of Ab2 are to compete with antigens in vitro and to induce antigen-specific antibodies in vivo. 5) For instance, the anti-Id WJ02 used in this study could be verified to contain the internal image of CA125 epitope because of its ability to bind to the antigen-combining region of mAb MJ01, to inhibit the binding of CA125 to scFv-MJ01, and to induce CA125-specific antibody (Ab3) in rats (data not shown). However, cellular response is more crucial than humoral response in antitumor therapy.…”
Section: Discussionmentioning
confidence: 82%
“…[4][5][6] In these assays it is difficult to distinguish the internal image anti-Id from anti-Id which bind to the idiotopes near the paratope of Ab1 (Ab2γ). Since genetic restrictions on host immune responses to Ab2γ may exist, these selecting methods may limit the therapeutic usefulness of Ab2.…”
mentioning
confidence: 99%
“…Similar results were achieved by substituting Tris (2-carboxy-ethyl)-phosphineHCl and DMSO with reduced and oxidized glutathione, respectively. TF1 and TF2 were each shown by size-exclusion high-performance liquid chromatography to be a single peak of the expected molecular size (f150 kDa), by BIAcore to be bispecific for both histamine-succinyl-glycine and a rat antiidiotype monoclonal antibody to hMN-14 (25), and by competition ELISA to be equivalent to hMN-14 immunoglobulin G (IgG) and h679 Fab, reflecting the full retention of valency and binding affinity. Furthermore, TF1 and TF2 were found to be stable for at least 7 days when incubated at 37jC in human or mouse serum, and the superiority of TF2 as a pretargeting agent for diagnostic imaging has been shown in nude mice bearing carcinoembryonic antigen -expressing human colonic cancer xenografts (21).…”
Section: Bispecific Trivalent Structures Composed Of Three Stably Linmentioning
confidence: 99%